1999
DOI: 10.1002/(sici)1521-3935(19991001)200:10<2276::aid-macp2276>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of new ABA triblock copolymers with poly[3(S)-isobutylmorpholine-2,5-dione] and poly(ethylene oxide) blocks

Abstract: SUMMARY: ABA type block copolymers with poly[3(S)-isobutylmorpholine-2,5-dione] (PIBMD, A) and poly(ethylene oxide) (M -n = 6 000, PEO, B) blocks, PIBMD-b-PEO-b-PIBMD, were synthesized via ringopening polymerization of 3(S)-isobutylmorpholine-2,5-dione in the presence of hydroxytelechelic poly-(ethylene oxide) with stannous octoate as a catalyst. M -n of the resulting copolymers increases with increasing 3(S)-isobutylmorpholine-2,5-dione content in the feed at constant mole ratio of monomer (M) to catalyst (C)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 13 publications
1
23
0
Order By: Relevance
“…[25] In the polymerization of 3-(S)-isobutylmorpholine-2,5-dione in the presence of PEO and Sn(oct) 2 , racemization of the l-leucine residue does not occur either. [19,20] The intensity of the resonance at d = 4.62 ppm observed in the 1 H NMR spectrum of 4 is stronger than of that in the spectrum of 3, which indicates that racemization is more pronounced in 4 than in 3. The racemization of the l-valine residue during copolymerization of IPMD with PEO in the presence of CaH 2 was determined from 1 H NMR spectra and is listed in Table 1.…”
Section: Synthesis and Characterization Of Pipmd-b-peo-b-pipmd Copolymentioning
confidence: 99%
See 1 more Smart Citation
“…[25] In the polymerization of 3-(S)-isobutylmorpholine-2,5-dione in the presence of PEO and Sn(oct) 2 , racemization of the l-leucine residue does not occur either. [19,20] The intensity of the resonance at d = 4.62 ppm observed in the 1 H NMR spectrum of 4 is stronger than of that in the spectrum of 3, which indicates that racemization is more pronounced in 4 than in 3. The racemization of the l-valine residue during copolymerization of IPMD with PEO in the presence of CaH 2 was determined from 1 H NMR spectra and is listed in Table 1.…”
Section: Synthesis and Characterization Of Pipmd-b-peo-b-pipmd Copolymentioning
confidence: 99%
“…[19,28] The 19 F NMR spectrum of the block copolymer treated with TFAA shows only one peak at d = -75.78 ppm. It is noted that a resonance at -75.35 ppm, which would be due to PEO treated with TFAA, is absent.…”
Section: Synthesis and Characterization Of Pipmd-b-peo-b-pipmd Copolymentioning
confidence: 99%
“…[46] Using hydroxytelechelic ethylene oxide as the macroinitiator in combination with tin octoate as the catalyst an A-B-A triblock copolymer 88 with polydepsipeptide side blocks and a polyethylene oxide middle block was obtained. [47,48] The goal of our further investigation was to prepare poly(ester-amide)s based an b-hydroxy-acids and a-or eaminoacids. For the preparation of cyclic ester amide monomers 91 an alternative route was applied based on the ring-expansion reaction of N-(hydroxy-acyl)-amides 89 [49] (Eq.…”
Section: Cationic Ring-opening Polymerization Of Cyclic Carbamates; Pmentioning
confidence: 96%
“…[1] The most convenient synthetic route for the preparation of polydepsipeptides is the ring-opening polymerization of the corresponding morpholine-2,5-diones. [2][3][4][5][6][7][8][9][10][11][12][13][14] The ringopening polymerization of morpholine-2,5-diones can be performed using both organometallic (typically tin(II)2-ethylhexanoate (Sn(Oct) 2 )) [2,4,6,15] as well as enzymatic catalysis. [9,10] Jörres et al, for example, have reported the preparation of polydepsipeptides based on (3S,6S)-3-isopropyl-6-methylmorpholine-2,5-dione with number-average molecular weights of up to 20 000 g Á mol À1 .…”
Section: Introductionmentioning
confidence: 99%